A Systematic Review of Clinical Practice Guidelines for Physical Therapist Management of Patellofemoral Pain. Issue 3 (3rd February 2021) - Wallis, Jason A; Roddy, Leanne; Bottrell, Judy; Parslow, Sue; Taylor, Nicholas F
Abstract: Objective: The purpose of this study was to conduct a systematic review to evaluate clinical practice guidelines for the physical therapist management of patellofemoral pain. Methods: Five electronic databases (CINAHL, Embase, Medline, Psychinfo, Cochrane Library) were searched from January 2013 to October 2019. Additional search methods included searching websites that publish clinical practice guidelines containing recommendations for physical therapist management of patellofemoral pain. Characteristics of the guidelines were extracted, including recommendations for examination, interventions, and evaluation applicable to physical therapist practice. Quality assessment was conducted using the Appraisal of Guidelines for Research and Evaluation (AGREE) II instrument, applicability of recommendations to physical therapist practice was examined using the AGREE Recommendation Excellence instrument, and convergence of recommendations across guidelines was assessed. Results: Four clinical practice guidelines were included. One guideline evaluated as higher quality provided the most clinically applicable set of recommendations for examination, interventions, and evaluation processes to assess the effectiveness of interventions. Guideline-recommended interventions were consistent for exercise therapy, foot orthoses, patellar taping, patient education, and combined interventions and did not recommend the use of electrotherapeutic modalities. Two guidelines evaluated as higher quality did not recommend using manual therapy (in isolation), dry needling, and patellar bracing. Conclusion: Recommendations from higher-quality clinical practice guidelines may conflict with routine physical therapist management of patellofemoral pain. This review provides guidance for clinicians to deliver high-value physical therapist management of patellofemoral pain. Impact: This review addresses an important gap between evidence and practice in the physical therapist management of patellofemoral pain. Lay Summary: If you have kneecap pain, this review offers guidance for your physical therapist to provide examination processes, treatments, and evaluation processes that are recommended by high-quality guidelines.